Development of Interactive Learning Media Based on an Articulate Storyline in Grade fourth of Elementary School - Iza Azizatul Baldah; Dodi Mulyadi; Testiana Deni Wijayatiningsih (UM Purwokerto Press, 2024)
On August 11st, 2022, In the ever-evolving digital era, the utilization of technology for educational purposes is becoming increasingly important. One of the latest innovations is the development of an Android app-based English learning media specifically designed to introduce basic concepts about three types of animals based on their food types. This study evaluates the impact of Articulate Storyline-based interactive learning media on grade 4 students. The results showed that the use of this media provided a number of benefits for students. They did not feel bored during the learning process and were able to distinguish three types of animals based on their food. This media also encourages independent and explorative learning, increases student engagement through interactive features, and helps teachers deliver material more effectively. Therefore, the use of this interactive learning media can be an effective solution to improve the quality of learning at the primary school level This app not only serves as a language learning tool, but also as an educational tool that invites users to understand the differences between herbivores, carnivores and omnivores in an interactive and engaging way. Through interactive features such as exercises and quizzes, users can access this learning material easily on their Android devices, making the learning process more effective and fun.